Effect of Wall Variable Thickness on Patient Specific Finite Element Abdominal Aortic Aneurysm Models - Altwijri, Omar (British Journal of Healthcare and Medical Research, 2018)
The aim of this study is to analyze the possibilities to measure the wall stress on the thinnest and thickest side of the AAA by using patient’s Specific Finite Element (SFE) models, in order for understanding the rupture of AAA in a better approach. Patient specific model with different in position, Finite Element Analysis (FEA) models that were studied earlier by Di Martino et al. (1998) [1], was adopted. The AAA was modelled as a homogenous, isotropic, incompressible, linear elastic material with Young’s modulus (E) and Poisson’s ratio (µ) having value of 0.11 MPa and µ = 0.45, respectively. The values of E and µ was determined from uniaxial loading tests performed on specimens of AAA. In order to cast peak systolic blood pressure of a healthy patient, pressure of 145 mmHg was directed to the internal surface of the models. FEA models of AAA were analysed using ANSYS Finite Element Package 15.0 version. Values of stress was observed on the scale of von-Mises, this method helps to locate area with highest stress i.e. to calculate failure criteria by combining the stress in three-dimensions. In order to determine the collapse of AAA wall von-Mises stress is commonly use for the assessment of the AAA stress. Our findings and results strengthens the earlier studies performed by Polzer et al. (2010) [2] and Altuwaijri (2015) [3], where AAA wall stress was reduced by formation of thrombus. Thus reducing the chance of AAA rupture and supporting the wall strength. Our findings suggest that thrombus clearly works as a shield to guard the AAA wall from rupture. However, more research and further studies are required that corroborate the relation between the biological and mechanical factors to understand the role of the thrombus for AAA rupture.